VOLATILES IN BASALTIC MAGMAS OF OCEAN ISLANDS AND THEIR MANTLE SOURCES: I. MELT COMPOSITIONS DEDUCED FROM MELT INCLUSIONS AND GLASSES IN THE ROCKS - Kovalenko V.I.; Girnis A.V.; Naumov V.B.; Dorofeeva V.A.; Yarmolyuk V.V. (My University, 2007)
Statistical analysis of a data bank of the compositions of glasses and melt inclusions in minerals from ocean-island basalts. The initial database contains more than 45 000 published analyses of ocean-island igneous rocks from around the world. Much attention was given to the contents of volatiles (H2O, Cl, F, and S) and their ratios to one another and to nonvolatile components of close incompatibility (Ti, P, K, and Ce). The average compositions of melt inclusions are similar to those of glasses of the rocks, including volatiles, with consideration for a somewhat higher degree (by approximately 20%) of the differentiation of glasses. The average compositions of ocean-island melts differ from those of mid-ocean basalts in having wider variations and elevated contents of some of the most incompatible elements (Sr, Nb, Ta, Ba, U, Th, and others), as well as H2O, F, and Cl. Based on the correlation of volatiles to one another and to incompatible elements, three groups of ocean-island basalts are distinguished: (I) low-K, P, Ti magma compositions approximating mid-ocean ridge magmas, (II) high-K, Ce, P, and Ti magmas that resemble continental rift magmas but differ from them in low H2O content, and (III) high-K, H2O, Ce, P, and Ti magmas close to continental rift magma. All three types of the melts were found only in the Hawaiian Archipelago, whereas other ocean islands are dominated by any one of these types. The distinguished melt types presumably reflect the differences (heterogeneity) in the compositions of the sources. © Pleiades Publishing, Ltd. 2007.